Conjunctival Dehiscence and Scleral Necrosis following Iodine-125 Plaque Brachytherapy for Uveal Melanoma: A Report of 3 Cases - Berry, Duncan E. (Ocul Oncol Pathol, 2018)
BACKGROUND/AIMS: Plaque brachytherapy is currently the most common treatment for uveal melanoma and has many known potential complications. Here we present 3 cases of early conjunctival and scleral necrosis following iodine-125 plaque. METHODS: This study was conducted as a retrospective case series. RESULTS: We identified 3 cases of early conjunctival and scleral necrosis following iodine-125 plaque. All patients were managed conservatively with resolution of the necrosis. CONCLUSIONS: While delayed corneoscleral necrosis following plaque brachytherapy has been previously reported, occurring many months to years after treatment, the 3 cases in this series presented within 2–6 weeks in the postoperative period. While we were unable to identify a specific etiology, we believe this represents a distinct clinical entity of post-brachytherapy cornea-scleral necrosis that is important to recognize. Possible causes include acute radiation toxicity, mechanical trauma, and/or conjunctival microinfection.